Parallelizable semidynamical systems - Pacifico, Tiago Alves (2021)
In this work, we introduce the concept of parallelizability for semidynamical systems. We study topological properties of impulsive and continuous parallelizable semidynamical systems. Two important relationships are investigated both in the study of continuous semidynamical systems and in the study of impulsive semidynamical systems: the relationship between parallelizable systems and the existence of sections and the relationship between parallelizable systems and dispersive systems. In addition, we present a study of parallelizability in the region of weak attraction of a compact, strongly invariant and asymptotically stable set. The new results presented in this thesis gave rise to the following articles: (1) Recursive properties on semidynamical systems: parallelizability and dispersiveness. See (BONOTTO; PACIFICO, 2021b). (2) Parallelizable impulsive semidynamical systems. See (BONOTTO; PACIFICO, 2021a).